Graphene-Based Materials for Bone Regeneration in Dentistry: A Systematic Review of In Vitro Applications and Material Comparisons - Azahara María Narváez-Romero; Francisco Javier Rodríguez-Lozano; María Pilar Pecci-Lloret (Nanomaterials)
Introduction: Graphene, a two-dimensional arrangement of carbon atoms, has drawn significant interest in medical research due to its unique properties. In the context of bone regeneration, graphene has shown several promising applications. Its robust structure, electrical conductivity, and biocompatibility make it an ideal candidate for enhancing bone tissue regeneration and repair processes. Studies have revealed that the presence of graphene can stimulate the proliferation and differentiation of bone cells, thereby promoting the formation of new bone tissue. Additionally, its ability to act as an effective carrier for growth factors and drugs allows controlled release, facilitating the engineering of specific tissues for bone regeneration. Aim: To assess the efficacy of graphene in enhancing bone regeneration through in vitro studies, identify key safety concerns, and propose directions for future research to optimize its clinical applicability. Materials and methods: The present systematic review was carried out using the PRISMA 2020 guideline. A first search was carried out on 20 November 2023 and was later updated on 14 February and 15 April 2024 in the databases of PubMed, Scopus, and Web of Science. Those in vitro studies published in English that evaluated the potential for bone regeneration with graphene in dentistry and also those which met the search terms were selected. Furthermore, the quality of the studies was assessed following the modified CONSORT checklist of in vitro studies on dental materials. Results: A total of 17 in vitro studies met the inclusion criteria. Among these, 12 showed increased osteoblast adhesion, proliferation, and differentiation, along with notable enhancements in mineralized matrix formation. Additionally, they exhibited a significant upregulation of osteogenic markers such as RUNX and COL1 (p < 0.05). However, the variability in methodologies and a lack of long-term assessments were noted as critical gaps. Conclusions: The evaluation of the efficacy and safety of graphene in bone regeneration in dentistry revealed significant potential. However, it is recognized that clinical implementation should be approached with caution, considering identified areas of improvement and suggestions for future research. Future studies should focus on standardized experimental designs, including in vivo studies to evaluate long-term safety, immune responses, and vascularization processes in realistic biological environments.